2008
DOI: 10.1111/j.1742-7924.2008.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing emotional distress in nurses using cognitive behavioral therapy: A preliminary program evaluation

Abstract: Introduction: Workplace stress among nurses has been associated with high absenteeism, low work satisfaction, and poor retention rates. Aim: This pilot study evaluated the effectiveness of a 1 day stress management program on nurses' stress levels. Methods: The nurse participants attended an 8 h face-to-face interactive workshop based on cognitive behavioral therapy. The subjects also were given a self-directed manual with reading and exercises to use after the workshop. The nurses were assessed at baseline an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Numerous studies have indicated that cognitive behavioral therapy is effective in modifying dysfunctional cognitions and improving an individual's ability to deal with stressful events (Mok et al, 2014; Moeini et al, 2011; Granath et al, 2006). As cognitive behavioral therapy focuses on modifying dysfunctional cognitions and promoting the adoption of appropriate behaviors for coping with stress and emergent situations, it can be especially effective for addressing the stress experienced by nurses (Brunero et al, 2008; Orly et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that cognitive behavioral therapy is effective in modifying dysfunctional cognitions and improving an individual's ability to deal with stressful events (Mok et al, 2014; Moeini et al, 2011; Granath et al, 2006). As cognitive behavioral therapy focuses on modifying dysfunctional cognitions and promoting the adoption of appropriate behaviors for coping with stress and emergent situations, it can be especially effective for addressing the stress experienced by nurses (Brunero et al, 2008; Orly et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Lang, Pfister, and Siemens (2010) found that both army and civilian nurses who experienced emotional exhaustion and depersonalization experienced burnout. In a promising pilot study, Brunero, Cowan, and Fairbrother (2008) studied how cognitive behavioral therapy (akin to rational nursing) reduced emotional distress in nurses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite CBT being the best validated approach for the treatment of stress [16-19], further clinical research is needed to refine existing protocols and fully exploit its clinical potential. Stress-related disorders cannot be explained simply on the basis of the terrible things that happen to people.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the Cochrane database underlines that “the poor quality of trials, considerable heterogeneity observed between trials and evidence of significant publication bias make the pooled findings insecure.” In other words, even if CBT is the best-validated approach for the treatment of stress [16-19], further clinical research is needed to tune existing protocols and fully exploit its clinical potential.…”
Section: Introductionmentioning
confidence: 99%